2010
DOI: 10.1128/jcm.01894-09
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Spoligotypes in Monterrey, Mexico

Abstract: Although tuberculosis is still a public health problem in Mexico, there is little information about the genetic characteristics of the isolates. In the present study, we analyzed by spoligotyping 180 Mycobacterium tuberculosis clinical isolates from the urban area of Monterrey, Mexico, including drug-susceptible and drug-resistant isolates. The spoligotype patterns were compared with those in the international SITVIT2 spoligotyping database. Four isolates presented spoligotype patterns not found in the databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
32
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 23 publications
9
32
0
1
Order By: Relevance
“…In a molecular analysis of M. tuberculosis DNA from a family of 18th century Hungarians two spoligotypes were identified, corresponding to SIT50 and SIT53 [25]. As in our study SIT53 is found in elderly patients in other parts of the world: in a study from Venezuela, patients with SIT53 had a significantly higher mean age compared to all other patients [26], and in Mexico SIT53 was significantly more prevalent in elderly patients, especially in females [27]. Polymorphism in the direct repeat region in clinical isolates appears to be the result of successive deletions of single discrete direct variant repeats (DVRs) or of multiple contiguous DVRs from a primordial direct repeat region [28].…”
Section: Discussionsupporting
confidence: 77%
“…In a molecular analysis of M. tuberculosis DNA from a family of 18th century Hungarians two spoligotypes were identified, corresponding to SIT50 and SIT53 [25]. As in our study SIT53 is found in elderly patients in other parts of the world: in a study from Venezuela, patients with SIT53 had a significantly higher mean age compared to all other patients [26], and in Mexico SIT53 was significantly more prevalent in elderly patients, especially in females [27]. Polymorphism in the direct repeat region in clinical isolates appears to be the result of successive deletions of single discrete direct variant repeats (DVRs) or of multiple contiguous DVRs from a primordial direct repeat region [28].…”
Section: Discussionsupporting
confidence: 77%
“…n a previous work, we described the spoligotype distribution in Nuevo León, Mexico, and reported that spoligo international type 53 (SIT53) and SIT119 were the most common spoligotypes to be isolated (representing ϳ39% of the total sample) (1). We also reported the tendencies of SIT53 to be isolated more frequently in elderly patients and of SIT119 to be isolated more frequently in younger patients (Ͻ20 years old).…”
mentioning
confidence: 79%
“…The Euro-American lineage of M. tuberculosis predominates in Mexico [11], where some areas also have high frequencies of the Indo-Oceanic lineage [12]. In Mexico M. bovis also appears to be a relevant cause of pulmonary TB (PTB) in humans [13,14], and the Beijing family of the M. tuberculosis East-Asian lineage has been mentioned in a recent paper [5].…”
Section: Introductionmentioning
confidence: 99%